(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The methodological recommendation presents the features of the use of different methods of the maxillofacial region for various deformities of the face. In recent decades, reconstructive and restorative operations are increasingly becoming an integral part of the treatment of patients with aesthetic deficiencies in various parts and areas of the body. The increasing interest of patients in restoring an aesthetically acceptable appearance prompts surgeons to introduce new techniques of reconstructive interventions. One of the promising directions in reconstructive surgery is the transplantation of one's own (autologous) adipose tissue (lipofilling), the interest in which among surgeons and patients has recently increased significantly. Lipofilling is a method of surgical removal of autologous adipose tissue from areas of excessive fat accumulation in order to correct the volume, shape of the contours or replace soft tissue defects in other anatomical areas of the so-called areas of interest. The autofat transfer technique has a history of over 100 years. The guidelines are intended for dentists, medical researchers, masters and clinical residents.